2021
DOI: 10.1109/oajpe.2021.3118445
|View full text |Cite
|
Sign up to set email alerts
|

Active Power Curtailment in Power System Planning

Abstract: In regions with high penetration of Distributed Energy Resources (DER), grid congestion is mostly caused by power feed-in of generators. In this context, conventional approaches for solving the grid congestion problems are Active Power Curtailment (APC) of DER and grid reinforcement. In the wake of increased DER generation, it is not only of interest how to obtain the grid reinforcement, but also how to consider APC during grid planning. The challenge of such grid planning is to determine the best combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 23 publications
(37 reference statements)
0
11
0
Order By: Relevance
“…To this end, we use AC distribution factors for bus voltage and branch current that enable us to define the LP optimization problem. Linear programming is a common way to formulate OPF problems [1–3, 23, 24]. Our method iteratively applies the solutions of LP problems until the AC‐OPF problem is solved.…”
Section: Security‐constrained Temperature‐dependent Optimal Power Flowmentioning
confidence: 99%
See 3 more Smart Citations
“…To this end, we use AC distribution factors for bus voltage and branch current that enable us to define the LP optimization problem. Linear programming is a common way to formulate OPF problems [1–3, 23, 24]. Our method iteratively applies the solutions of LP problems until the AC‐OPF problem is solved.…”
Section: Security‐constrained Temperature‐dependent Optimal Power Flowmentioning
confidence: 99%
“…The branch admittance matrix allows to calculate the branch‐related distribution factors that describe the linear dependency between branch power flows and bus power injections [2, 23]. In addition, the dependency of the current through branch ft$ft$ on the power injection at bus K DFIft=dIftdPk${DF_{I}}_{ft}=\frac{dI_{ft}}{dP_k}$ can be obtained by applying the chain rule, as described in more detail in reference [24]. The values of the so‐defined AC distribution factors are valid at or close to the operational point of the converged AC power flow.…”
Section: Security‐constrained Temperature‐dependent Optimal Power Flowmentioning
confidence: 99%
See 2 more Smart Citations
“…Distribution system operators can postpone network upgrades by, for example, optimally curtailing the energy during a few worst-case hours causing network violations. Thus, the underlying economic aspects of different approaches were analysed in the literature and the authors of [23] found the optimal combination of curtailment and upgrade. Moreover, curtailment was seen as not only the loss of clean energy but as an inevitable revenue loss for the PV owners [24].…”
Section: Introductionmentioning
confidence: 99%